Enfermedad de Kawasaki: A propósito de un caso atípico y con intususcepción. - TORI TORI, Carlos; BAZÁN ZENDER, Carlos; VARGAS GALGANI, Mario (Revista Médica Herediana, 2013)
We present a rare association of atypical Kawasaki disease and intussusception in a three month old male patient. It all began with high fever and an obstructive intestinal syndrome developed in the second day of hospitalization, diagnosed as a colo-colonic intussusception. Despite an adecuate postoperative antibiotic coverage the high fever continued, which made us pursue a diagnosis of a vasculitis syndrome among other entities. The echocardiogram showed dilatation of both coronary arteries. The currently accepted clinical criteria for Kawasaki disease may not always allow its identification in patients who are younger than six months of age. A diagnosis of Kawasaki disease and an echocardiographic evaluation of the coronary arteries should be considered in young infants with prolongued fever of unkown origin. ( Rev Med Hered 2001; 12: 37-41 ).